A novel seed/buffer-layer construction for enlarging c-directional growth sector in high performance YBa2Cu3O7−δ bulk. (June 2018) - Qian, Jun; Ma, Ling Tian; Du, Ge Hai; Xiang, Hui; Liu, Yan; Wan, Yan; Huang, Si Min; Yao, Xin; Xiong, Jie; Tao, Bo Wang
Abstract: The size enlargement of the c -growth-sector ( c -GS) is a matter of great importance in fabricating high-performance YBa2 Cu3 O7−δ (Y123) bulks. Here, we report a novel construction of film-seed/buffer-layer/main-pellet, in which the 45°-aligned film-seed associated with a would-be [110]-sided buffer-layer was applied. The [110]-sided seed rapidly induced the crystallization of the buffer-layer with the (110) face, which prompted the second rapid growth on the main-pellet. Consequently, an Y123 bulk with sizable c -GS and high levitation force was achieved. The new seeding construction with the rapid growth nature of non-equilibrium face is encouraging for preparing other superconductor bulks in the Y123 family. Graphical abstract: Unlabelled Image